Lentinula edodes, a Novel Source of Polysaccharides with Antioxidant Power (2022)
ABSTRACT: : The fruiting bodies of edible mushrooms represent an important source of biologically active polysaccharides. In this study, Lentinula edodes crude polysaccharides (LECP) were extracted in hot water, and their antioxidant and antiradical activities were investigated. The antioxidant activity of LECP was investigated against reactive species such as 1,1’-diphenyl-2-picrylhydrazyl, 2,2’- azino-bis(3-ethylbenzothiazoline-6-sulfonic acid, hydroxyl and superoxide anion radicals, reducing power with EC50 values of 0.51, 0.52, 2.19, 3.59 and 1.73 mg/mL, respectively. Likewise, LECP inhibited the lipid peroxidation induced in methyl linoleate through the formation of conjugated diene hydroperoxide and malondialdehyde. The main sugar composition of LECP includes mannose, galactose, glucose, fucose and glucuronic acid. Characterization by Fourier transform infrared spectroscopy and nuclear magnetic resonance determined that LECP was made up of α and β glycosidic bonds with a backbone of α-D-Glc, →6)-β-D-Glcp-(1→, →6)-α-D-Galp-(1→ and β-DManp-(1→ residues. The results showed that LECP can scavenge all reactive species tested in a concentration-dependent manner and with a protective effect in the initial and final stages of lipid peroxidation. The natural antioxidant activity of the LECP that was investigated strengthens the high medicinal and nutritional value of this mushroom